Nonlinear solid mechanics : bifurcation theory and material instability - Bigoni, Davide, 1959- (Cambridge : Cambridge University Press, 2012)
'This book covers solid mechanics for non-linear elastic and elastoplastic materials, describing the behaviour of ductile material subject to extreme mechanical loading and its eventual failure. The book highlights constitutive features to describe the behaviour of frictional materials such as geological media. On the basis of this theory, including large strain and inelastic behaviours, bifurcation and instability are developed with a special focus on the modelling of the emergence of local instabilities such as shear band formation and flutter of a continuum. The former is regarded as a precursor of fracture, while the latter is typical of granular materials. The treatment is complemented with qualitative experiments, illustrations from everyday life and simple examples taken from structural mechanics'--
Includes bibliographical references (pages 507-525) and index.
Keywords: Nonlinear mechanics; Materials -- Mechanical properties; Elastic analysis (Engineering).; Bifurcation theory